Pengaruh Substitusi Tepung Ubi Ungu dan Lama Penyimpanan Terhadap Kadar Air dan Jumlah Total Mikrobia Pada Bolu Kukus - Pratiwi, Nikien; , Eni Purwani, S.Si., M.Si; , Siti Zulaekah, A., M.Si (2016)
Sponge cake is a product made from wheat flour. Wheat flour consumption tends to increase every year, therefore it needs to reduce the dependence on wheat flour consumption by utilizing the purple sweet potato that is converted into flour. Purple sweet potato flour rich in antioxidant, low glycemic index and hygroscopic that can affect the water content and the total microbial count. The purpose of this study to determine the effect of purple sweet potato flour substitution and length storage with water content and total microbial count in the sponge cake. The design of this study was a experimental method with completely randomized and factorial design. Variations substitution of purple sweet potato flour were 0%, 15%, 30% and 45%. Variations of storage time were 0 hours, 24 hours and 48 hours. The water content was tested by thermogravimetry method and the total microbial count were tested with TPC method. The water content and the total microbial count were analyzed using a Kruskal-Wallis and GLM-Univariate. Differences in the results were analyzed using Duncan test at 5% level. The results of the research show that the lowest water content of sponge cake on 15% purple sweet potato flour substitution (23,08%), while the lowest total microbial count of spange cake was on 15% substitution (2,86x106 cfu /ml). Based on the length of storage, the lowest water content was on 48 hours of storage time (23,64%), while the lowest total microbial count was on 0 hours of storage time (1,6x105 cfu/ml). There was the effect of purple sweet potato flour substitution with water content, while there was no effect of length storage on water content. There was no effect of purple sweet potato flour substitution on the total microbial count. However, there was the effect of storage time on the total microbial count on the sponge cake.